1992
DOI: 10.1016/0014-5793(92)80645-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory, carboxyatractylate‐sensitive uncoupling in heart and skeletal muscle mitochondria of the ground squirrel correlates with the level of free fatty acids

Abstract: Thermoregulatory uncoupling of oxidative phosphorylation has been studied in heart and skeletal muscle mitochondria of ground squirrels. The respiratory rate ofmitochondria in the presence of oligornycin was found to be much higher in winter (in hibernating, arousing, or aroused animals) than in summer. This additional respiration is strongly (arousing animals) or completely (hibernating and aroused anhnals) inhibited by carboxyntractylate (CAtr) and bovine serum albumin (USA). The CAtr-and BSA-induced decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
4
18
0
Order By: Relevance
“…pore formation, may be necessary. Again, as in the former mechanism, FFA may be a mediator of uncoupling since (a) mitochondrial FFA content increases during arousal of the hibernating animal [5], and (b) addition of palmitate to the mitochondria of aroused animals induces the CSA-sensitive uncoupling (see Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pore formation, may be necessary. Again, as in the former mechanism, FFA may be a mediator of uncoupling since (a) mitochondrial FFA content increases during arousal of the hibernating animal [5], and (b) addition of palmitate to the mitochondria of aroused animals induces the CSA-sensitive uncoupling (see Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Such measurements might include in vivo NMR of the high energy compounds and in situ studies of morphology of mitochondria. In this connection, one may mention that the [FFA] increase during arousal of ground squirrels was shown not only in isolated mitochondria but also in tissues [5].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many of the studies in hibernators have only examined mitochondria isolated from liver, and when additional tissues have been investigated, results have been mixed. Hannon et al (22) found that respiration of skeletal muscle homogenates was depressed in hibernating arctic ground squirrels (Spermophilus parryii), whereas Brustovetsky et al (11) found that heart and skeletal muscle mitochondrial respiration was increased in hibernating compared with active arctic ground squirrels. If metabolic depression is tissue specific, this may account for the discrepancy between whole animal and mitochondrial studies, as whole animal oxygen consumption is a composite of total metabolic activity and may fail to resolve mitochondrial activity among individual tissues.…”
mentioning
confidence: 98%
“…Respiration rates of isolated mitochondria measured at 37°C are lower in ground squirrels during torpor in liver but not skeletal muscle compared with summer active controls (33, 50). However, there are clear indications of seasonal (i.e., summer vs. winter) metabolic cycles in hibernators that are distinct from the torpor-arousal cycle (16,51). In addition, hibernators do not feed throughout the winter but do feed throughout the summer, which could have effects on mitochondrial properties (11,67).…”
mentioning
confidence: 99%